The Feminine Aspect in Islamic Spirituality (A Study of the Thought of Annemarie Schimmel) - Umi, Umi; Dzawafi, Agus Ali; Hafidz Taqiyuddin (Jurnal Ar Ro'is Mandalika (Armada), 2025)
This research aims to explain the feminine aspect in Islamic spirituality by using the study of Annemarie Schimmel's thoughts. The term feminine is generally interpreted as a trait, a characteristic possessed by women. In the context of Sufism, the terms feminine and masculine do not lie in literal gender, but rather in the characteristics or spiritual traits that are considered to have traits that are often identified with the concept of feminine or masculine. The type of research used in this study is a pure type of library research that examines various related information from both primary data sources (primary source) and supporting data sources (second source). The results of this study explain that women have a very important role in Sufism. The attributes of Jalal and Jamal are two aspects of Allah's attributes towards His Essence. This is what Annemarie Schimmel's thinking is based on, she shows various feminine elements, such as the archetype of the soul (nafs) which is represented and embodied in the form of a woman, because nafs in Islam has several meanings associated with traits that are considered female characteristics. In the Quran for example, nafs can mean “soul” that incites evil (QS Yusuf: 53), “accusing soul” (QS al-Qiyamah :2), or “peaceful soul” (QS al-Fajr: 27-28).